Armazenamento de sementes germinadas de Handroanthus heptaphyllus (Vell.) Mattos e seu comportamento em viveiro - Caldas, Isliana Griebler Ribeiro [UNESP] (2015)
The research aimed to extend the maintenance of viability and longevity of Handroanthus heptaphyllus (Vell.) Mattos seeds for periods longer than the conventional storage procedures, via seeds. For that, we tested the storage procedure by germinated seeds. The objective of this work was to store germinated seeds of H. heptaphyllus (Study 1); and try to extend still more the storage period through the re-induction of primary root tolerance desiccation by polyethylene glycol (PEG) treatment (Study 2). We also aimed to evaluate the development of young plants of germinated seeds. The storage was performed in a cold chamber (10 ° C) into the substrate with three levels of water retention capability (0, 30, and 60%). The germinated seeds were evaluated monthly through nine months under the germination chamber environment, at 25° C with 8 hous light /day (for 30 days), and then, following to the nursery for monitoring their development (greenhouse - 30 days; shade house - 30 days; and sunlight - 45 days). It was possible to store ipê germinated seeds, as well as to restore the desiccation tolerance of those. The results have shown that is possible to store germinated seeds into the 0% of humidity for 7 months, with approximately 50% of survival. Yet the germinated seeds treated with PEG, showed no extended storage period due to the high mortality during the months long. In both studies, the survival and the development of normal seedlings decreased over the time. Based on the results we can conclude that the storage of germinated seeds did not prolong the viability of ipê. More studies are needed to better adapt the methodology to store this species ...